Creating a Culture for Low Carbon Innovation Adoption: A Case Study of Boots UK - Erlenbach, Adrian (2012)
The purpose of this dissertation is to explore the sustainability innovation process in large organizations by investigating the cultural systems that facilitate the adoption of low-carbon innovations at Boots. Taking a single-case approach, this dissertation examines the nature and content of the cultures and subcultures that exist in Boots’ head office and retail locations to gain insight into the social context mediating Boots’ low-carbon innovation efforts.